Analisis Efektivitas Penanggulangan Tindak Kejahatan Jalanan di Wilayah Hukum Polres Tangerang Selatan - Mahendra Tri Octavianus; Eva Achjani Zulfa; Indriyanto Seno Aji (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The police are one of the many law enforcement officers who have the authority to carry out investigation and investigation duties for all criminal cases. Street crime is one of the many crimes classified as a criminal element that is still developing in society and often causes disturbances in security and order. The COVID-19 pandemic gives an indication of a significant increase in street crime, including in the jurisdiction of the South Tangerang Police. This study tries to see the effectiveness of law enforcement, especially the prevention of street crime from the pre-emptive aspect in the jurisdiction of the South Tangerang Police and identify important factors that affect.